A monumental Hellenistic funerary ensemble at Callatis on the Western Black Sea. - Sîrbu, Valeriu,; Ștefan, Marian,; Ștefan, Dan, (Archaeopress Archaeology, 2021)
Documaci Tumulus, a spectacular early Hellenistic funerary monument recently excavated on the western Black Sea coast, was built at the threshold of the 4th to 3rd centuries BC in the cemetery of the Greek City of Callatis. Excavations offer a glimpse into a complex and interconnected world of Hellenistic architects and artists.